A-TIG welding process for enhanced-penetration in Duplex stainless-steel: effect of activated fluxes. Issue 15 (18th November 2019) - Tathgir, Surinder; Rathod, Dinesh W.; Batish, Ajay
ABSTRACT: Weldability of duplex stainless steel (DSS) is an important issue in fabrication of pipes at petrochemical industries. Well-established tungsten inert gas (TIG) welding process has the limitations of lesser penetration; however, process parameters (such as current and voltage) need to increase to attain deeper penetration, which, in turn, affects the material's property owing to increased heat energy. Use of activated fluxes generate the extra heat energy with same process parameters and causes the deeper penetration and increased dilution. The aim of the present study is to investigate the effect of activated fluxes on penetration, dilution, weld chemistry, weld microstructure, gas and slag metal reactions which has resulted from extra heat energy produced. Different activated fluxes were investigated in context of heat energy, associated penetration, dilution and weld pool properties. The oxygen content in activated flux has played significant role in hot cracking and void formations in the weld. Similarly, it also changes the surface tension gradient of weld pool considerably. Dendrite growth is predominant in oxide-based fluxes and this growth in austenite and ferrite dendrite has been evidenced as a function of oxygen content. The process with relevant mechanisms is elaborated in the present study.